1995
DOI: 10.1038/375581a0
|View full text |Cite
|
Sign up to set email alerts
|

Persistent DDT metabolite p,p'–DDE is a potent androgen receptor antagonist

Abstract: The increase in the number of reports of abnormalities in male sex development in wildlife and humans coincided with the introduction of 'oestrogenic' chemicals such as DDT (1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane) into the environment. Although these phenotypic alterations are thought to be mediated by the oestrogen receptor, they are also consistent with inhibition of androgen receptor-mediated events. Here we report that the major and persistent DDT metabolite, p,p'-DDE (1,1-dichloro-2,2-bis(p-chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
571
7
13

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,411 publications
(618 citation statements)
references
References 26 publications
19
571
7
13
Order By: Relevance
“…In adolescents, the observed association of HCB with higher sex hormone levels (Dhooghe et al, 2009) might be the dominant effect in adolescents and might cause the quite strong negative association between HCB serum level and BMI , whereas the antiandrogenic characteristics of p,p'-DDE (Kelce et al 1995;Li et al 2008) and the antiandrogenic and anti-oestrogenic characteristics of HCB (Li et al 2008) might be dominant mechanisms in adults, causing the (for HCB strong) positive association with BMI. That HCB might in addition induce a slightly hypothyroidal status (Foster et al, 1993;Meeker et al 2007) might contribute to a positive association with BMI as a significant negative association between serum HCB concentration and free triiodothyronine was indeed observed in the adolescents participating in this study (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adolescents, the observed association of HCB with higher sex hormone levels (Dhooghe et al, 2009) might be the dominant effect in adolescents and might cause the quite strong negative association between HCB serum level and BMI , whereas the antiandrogenic characteristics of p,p'-DDE (Kelce et al 1995;Li et al 2008) and the antiandrogenic and anti-oestrogenic characteristics of HCB (Li et al 2008) might be dominant mechanisms in adults, causing the (for HCB strong) positive association with BMI. That HCB might in addition induce a slightly hypothyroidal status (Foster et al, 1993;Meeker et al 2007) might contribute to a positive association with BMI as a significant negative association between serum HCB concentration and free triiodothyronine was indeed observed in the adolescents participating in this study (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…PCBs are known to have estrogenic, anti-estrogenic and antiandrogenic activities (Bonefeld-Jorgensen et al, 2001); p,p'-DDE was reported to have antiandrogenic properties (Kelce et al, 1995); HCB was reported to affect oestradiol levels in animals (Alvarez et al, 2000;Foster et al, 1995) and to interact with hormone receptors (Li et al, 2008); cadmium was observed to be able to interact with both oestrogen and androgen receptors (Stoica et al, 2000;Martin et al, 2002); lead was reported to have xenoestrogenic activity (Martin et al, 2003) and to affect pubertal development in girls (Selevan et al, 2003); polycyclic aromatic hydrocarbons were reported to affect development (Choi et al, 2006) and display as well AhR as estrogen receptor-mediated activity (Hilscherova et al, 2000). We wanted to test the hypothesis that low differences in levels of internal exposure (such as these occurring in the general population in Flanders) to endocrine disrupting substances result in differences in body size parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Individual exposure varies with dietary habits, life style, and work. Most of these pollutants are lipophilic and are stored in body fat for a lifetime [83]. They are also found in breast milk [84] and in the amniotic fluid.…”
Section: Ii-3 Contamination Routesmentioning
confidence: 99%
“…Both RA and HVC contain a high prevalence of androgen receptors (Gahr, 2001;Metzdorf et al, 1999), and testosterone has been shown to increase the size of these brain structures (Alvarez-Borda and Nottebohm, 2002;Ball et al, 2002). Thus, the ability of p,p'-DDE to act as potent androgen receptor antagonist (Kelce et al, 1995) may explain the effects of p,p'-DDE on brain structure size (Iwaniuk et al, 2006). Chemicals found in the pesticide chlordane (e.g., cis-nonachlor, trans-nonachlor, cis-chlordane, and transchlordane) are neurotoxicants that block the λ-aminobutyric acid (GABA) receptor found in the brain.…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%